Dual Microscope Indocyanine Green Video Angiography and Endoscopic Review to Treat Intracranial Aneurysm: A Review of the Literature Regarding a Case - Vega-Moreno, Daniel Alejandro; Janković, Dragan; Azouz, Heba; Nakipuria, Mayank; Kato, Yoko (Asian Journal of Neurosurgery, 2023)
The use of the indocyanine green video angiography (ICG-VA) both endoscope and microscope has become popular in recent decades thanks to the safety, efficacy, and added value that they have provided for cerebrovascular surgery. The dual use of these technologies is considered complementary and has helped cerebrovascular surgeons in decision-making, especially for aneurysm clipping surgery; however, its use has been described for both aneurysm surgery, resection of arteriovenous malformations, or even for bypass surgeries. We conducted a review of the literature with the MeSH terms “microscope indocyanine green video angiography (mICG-VA),” “endoscopic review,” AND/OR “intracranial aneurysm.” A total of 97 articles that included these terms were selected after a primary review to select a total of 26 articles for the final review. We also present a case to exemplify its use, in which we use both technological tools for the description of the aneurysm, as well as for decision-making at the time of clipping and for reclipping. Both tools, both the use of the endoscope and the mICG-VA, have helped decision-making in neurovascular surgery. A considerable clip replacement rate has been described with the use of these technologies, which has helped to reduce the complications associated with poor clipping. One of the main advantages of their usefulness is that they are tools for intraoperative use, which is why they have shown superiority compared to digital subtraction angiography, which takes longer to use and has a higher risk of complications associated with the contrast medium. On the other hand, a very low rate of complications has been described with the use of the endoscope and mICG-VA, which is why they are considered safe tools to use. In some cases, mention has been made of the use of one or the other technology; however, we consider that its dual use provides more information about the status of the clip, its anatomy, its relationship with other vascular structures, and the complete occlusion of the aneurysm. We consider that the use of both technologies is complementary, so in case of having them both should be used, since both the endoscope and the mICG-VA provide additional and useful information.
Keywords: microscope indocyanine green video angiography; endoscopic review; intracranial aneurysm; aneurysm clipping; cerebrovascular surgery